Military-security practices influence the United States in Iraq - Jalal Derakhshe; Amir Reza Jafari Harandi (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2017)
The US struggled to achieve its pre-determined purposes using smart management of different power resources through the attck on Iraq in 2003. So, one of the main strategies of the US would be the penetration into Iraq structures to obtain America's aims. This study investigates the behavior of the US' management on hard power resources inside Iraq. Therefore, the current study has been written in respone to a question statting what are the coordinates of the US' hard penetration in new Iraq? and follows consideration of penetration methods of the US with focusing on existance period of the US soldiers. Inspecting of librarian sources and environmental events depict the US is trying to penetrate in security-military structures of Iraq with applying arms treaties (with justification of struggle for strengthening Iraq's defense power), equipping the central government' opponents, using the capacity of private security companies, and furthermore financial assistances in order to be able to achieve its interests and benefits in local and international levels.